Scanpath EEG dynamic, a new perspective for neuroaesthetic connoisseurship in paintings - Cheron, Guy; De Maere, Jan (Frontiers in Psychology, 2025)
The analysis of ocular scanpaths during the observation of artistic pictures has paved the way for neuroaesthetics to question the involvement of brain mechanisms during artistic experiences. In this review, we revisit the main aspects of three fundamental domains of investigation implicated in the perception of art and beauty: (1) oculomotor science, (2) vision, and (3) the dynamics of brain oscillations. For each of these fields, central elements are highlighted to demonstrate their functional inter-dependency for the future development of neuroaesthetics, upon which connoisseurship expertise depends. Namely, the scanpath theory, linked to basic neurophysiological concepts such as saccadic and blink suppression, fixational eye movements, and sensorimotor mnemonic, were described and integrated with other important elements of visual search. The meaning, saliency, and integrated priority maps were discussed in relation to working memory and consciousness. Then, the basic and specialized networks of the visual framework were reviewed in relation to bottom-up, top-down, and corollary discharge mechanisms. Finally, the EEG dynamics of alpha and gamma oscillations were proposed to decipher the involvement of brain wave generators during scanpath artistic exploration.